DISASTER RISK FINANCING AND INSURANCE: HOW FAR HAVE WE KNOWN? - Amalia Adhasara; Resi Ariyasa Qadri; Rachma Aprilia (Center for Economic Studies Universitas Katolik Parahyangan, 2022)
Natural catastrophes have resulted in massive losses for Indonesia. The government lacks the capacity to pay all damages caused by the disasters. The purpose of this research is to map the literature on catastrophe risk finance and insurance, particularly in terms of financial instruments that can be deployed. The scoping review approach was used in this study to locate and map relevant material. The findings of this study revealed that there are still significant research gaps on the issue of catastrophe risk finance and insurance, beginning with the research aim, financial instruments mentioned, and research methodologies and procedures applied. This study is planned to serve as the foundation for future research on the subject of catastrophe insurance in developing nations.